Biochar influence on the development of spring wheat (Triticum aestivum L.) and acidity of soddy-podzolic soil in Western Siberia - K. O. Ponomarev; A. N. Pervushina; K. S. Korotaeva; A. A. Yurtaev; A. S. Petuhov; R. B. Tabakaev; I. I. Shanenkov (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
The paper purpose was to establish the effect of applying biochar obtained from various organic wastes of agriculture (cow manure, straw), woodworking (pine sawdust) and food industry (pine nut shell), which are typical of Western Siberia, on the morphometric characteristics of plants (using spring wheat (Triticum aestivum L.) as the example) and the soddy-podzolic soil properties. The assessment of biochar influence was performed by a series of vegetation experiments using climatic chambers. As a result, it was found that the introduction of all the noted biochar types into the soil layer leads to a significant (p < 0.05) increase in the morphometric characteristics of spring wheat. For example, when applying the straw biochar to the soil, it results in growing the plant height to the node by 19%, while the number of leaves increased by 8% compared to the control variant. The introduction of biochar from manure leads to the increased length of the spring wheat root by 35%. Moreover, straw and manure biochars contribute to the reduction of soil acidity (increase in pH values from 7.1 to 7.4 and 7.8, respectively). The results of the comprehensive analysis indicate that the agronomic advantages of application of biochars obtained from wheat straw and cattle manure are better compared to biochars from pine sawdust and pine nut shells, which is due to higher concentration of nutrients and substances with alkaline reaction (carbonates and oxides) in the former. The results obtained are useful from the point of view of assessing the environmental risks when applying biochar ameliorants in soils typical of the boreal bioclimatic zone. Subsequent experiments, including studies of the joint application of biochars and fertilizers to the soil, will make it possible to develop recommendations for applying the thermal conversion technology for recycling the regional organic waste into ameliorants that improve soil quality and increase its fertility.